1998
DOI: 10.1007/s004310050810
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of large low density lipoprotein particles and lower fractional esterification rate of cholesterol in high density lipoprotein in children with insulin-dependent diabetes mellitus

Abstract: The qualitative and quantitative changes in LDL and HDL in diabetic children are similar to those associated with a reduced risk for CAD. Intensive insulin therapy in children may help preventing coronary heart disease in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 42 publications
2
10
0
3
Order By: Relevance
“…22 In various studies, HbA1c level was eminent as showing positive correlation with TC, LDL and TGL in diabetic patients. [30][31][32] HbA1c also demonstrated direct and significant correlations with cholesterol (r=0.6445), TGL (r= 0.5426), LDL-C(r=0.3584), VLDL (r=0.2245) -a strong positive correlation; whereas HDL-C showed negative correlation (r=-0.4965). 9 Jayesh et al conducted a prospective study on western Indian population that comprised of 430 T2DM patients and 501 non-diabetic control subjects.…”
Section: Discussionmentioning
confidence: 91%
“…22 In various studies, HbA1c level was eminent as showing positive correlation with TC, LDL and TGL in diabetic patients. [30][31][32] HbA1c also demonstrated direct and significant correlations with cholesterol (r=0.6445), TGL (r= 0.5426), LDL-C(r=0.3584), VLDL (r=0.2245) -a strong positive correlation; whereas HDL-C showed negative correlation (r=-0.4965). 9 Jayesh et al conducted a prospective study on western Indian population that comprised of 430 T2DM patients and 501 non-diabetic control subjects.…”
Section: Discussionmentioning
confidence: 91%
“…Ohta et al 21 reported significantly greater HDL and LDL particle sizes in T1D children compared to healthy control subjects. In contrast, Alabakovska et al 22 showed that despite an absence of significant differences in the plasma lipid profiles between T1D children and controls, the concentration of sdLDL was increased and mean LDL particle size was smaller in subjects with T1D.…”
Section: Discussionmentioning
confidence: 96%
“…It plays a key role in reverse cholesterol transport and is activated by the apoA-I in HDL [16]. The impact of diabetes on the ability of HDL to act as a substrate for LCAT is unclear, with reports suggesting that it either diminishes [17], does not alter [18] or increases the rate of LCATmediated cholesterol esterification [19]. These discrepancies are probably due to variations in the study populations and the methods used to measure cholesterol esterification [15].…”
Section: Introductionmentioning
confidence: 99%